Do Audit Partner and Audit Committee Member Ideologies Influence Engagement Partner Selection and Financial Reporting Oversight Effectiveness? - Felix, Robert; Mansi, Sattar; Pevzner, Mikhail; Seidel, Timothy (Contemporary Accounting Research, 2026)
ABSTRACT This study examines whether the ideological orientation of the audit partner and audit committee members—defined as their personal belief systems and inclinations, including their attitude toward risk, ambiguity, and novelty—has an impact on engagement partner selection and the effectiveness of oversight in the financial reporting process. Drawing on prior evidence that the two main US political parties reflect different ideologies, we hand‐collect political donation data to construct ideological scores for audit partners and audit committee members. Our findings highlight several intriguing relationships. First, audit committees are more likely to select an ideologically dissimilar partner. Second, greater ideological dissimilarity between these two key monitors is associated with higher financial reporting quality. The effects of financial reporting quality are most pronounced among more effective audit committees and when audit partners have longer tenure with the client. These effects are incremental to both social connections between the audit partner and audit committee and to ideological differences between these parties and the CEO and CFO. Overall, the results support the notion that ideological dissimilarity between audit partners and audit committees can foster effective oversight of the financial reporting process. Moreover, ideological dissimilarity appears to be a useful and rational cue in audit partner selection decisions.